Endothelial immunomediated reactivity in acute cardiac ischaemia: Role of endothelin 1, interleukin 8 and NT-proBNP in patients affected by unstable angina pectoris. (September 2016) - Caroselli, Costantino; De Rosa, Rosario; Tanzi, Pietro; Rigatelli, Alberto; Bruno, Guglielmo
The role of endothelium in the progression of atheromasic disease has already been demonstrated. Endothelin-1 (ET-1) is released from endothelial cells during acute and chronic vascular damage and it appears to be the strongest vasoconstrictor agent known. The aim of this study is to investigate the amount of endothelial damage in patients with unstable angina (UA), as defined by serum levels of ET-1, to verify a possible correlation with increased ischaemic damage by evaluation of serum N-terminal pro-brain natriuretic peptide (NT-proBNP) and interleukin 8 (IL-8) levels. Serum levels of ET-1, IL-8 and NT-proBNP obtained from 10 patients affected by low-risk UA were compared to those belonging to eight healthy subjects. In order to compare the laboratory data pertaining to the two populations, a Student's t-test and a Mann-Whitney U test were performed. Levels of ET-1, IL-8 and NT-proBNP in samples of peripheral blood of patients affected by UA were significantly elevated, compared with those of the control group. The linear correlation analysis demonstrated a positive and significant correlation between levels of ET-1 and IL-8, between levels of ET-1 and NT-proBNP, and between levels of IL-8 and NT-proBNP in subjects affected by UA. Early elevated levels of ET-1, IL-8 and NT-proBNP in patients with UA show a coexistence between ischaemic insults and endothelial damages. A positive and significant linear correlation between levels of ET-1 and IL-8, between levels of ET-1 and NT-proBNP, and between levels of IL-8 and NT-proBNP confirms that an increased ischaemic insult is correlated to inflammation signs and endothelium damage signs. In patients with UA, ischaemia is always associated with a systemic immuno-mediated activity induced by acute endothelial damage. We suggest early administration of ET-1-selective receptor blockers and anti-inflammatory drugs.